Application of Islamic Culture History Learning Methods at Mi Muhammadiyah Semondo: Penerapan Metode Pembelajaran Sejarah Kebudayaan Islam Di Mi Muhammadiyah Semondo - Muhamad Mahali (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
The History of Islamic Culture is a lesson that examines the origins, development, role of Islamic culture and figures who excelled in Islamic history in the past, starting from the history of pre-Islamic Arab society, the history of the birth and apostolate of the Prophet Muhammad until the time of the Khulafaurrasyidin. Qualitative method, which is a research method that provides more analytical explanations and is subjective. The qualitative method uses research techniques in the form of observation and open interviews. Followed by literacy, namely finding sources from books, web journals. The background is to find out the methods used at MI Muhammadiyah Semondo. Aims to understand the method applied and how to implement it. Consists of the jiksaw method and make a mach